A modular system for prefabricated prefinished volumetric construction (PPVC) - member behaviour - Ng, Maggie (2015)
In recent years, Singapore’s Building and Construction Authority (BCA) has placed emphasis on the use of advanced and innovative construction technologies with the intention of moving towards sustainability and higher productivity. Prefabricated Prefinished Volumetric Construction (PPVC), also known as Modular Construction, is one of the game-changing technologies that has been adopted in Singapore due to its spectrum of advantages. This report aims to discuss Modular Construction in more detail, with a focus on its construction framework and design principles. In addition, two present-day modular systems will be described with their limitations being discussed. To minimise the problems caused by these limitations, the LT Steel Connection System is proposed in this report. This original connection system primarily constitutes of rectangular hollow section columns, I-beams, cruciform base, connecting plate and bolts. Composition of the connection varies according to its position on the module. As such, the LC-B, LC-SY, LC-SX, LC-Q, TC-B and TC-SX connections formed the entire connection system. A series of finite element models were established using a computer software program, ABAQUS, to investigate the rectangular hollow section column member behaviour in terms of its ultimate axial compressive strength upon loading. Further investigation was conducted to ascertain the compressive behaviour of connection type modelled with thick and thin cruciform base plate respectively. Analysis has shown that compressive stress was centralized at the cruciform base as well as the welded end of the column and beam. Due to cumulated compressive stress distributed to the welded end of the column, significant deformation was developed at this region. Graphical and numerical data have concluded that a thick cruciform base plate has greater capability in resisting a larger compression load. The remarkable difference between the analysis results and manually calculated design values suggests that the adoption of Eurocode 3, EN 1993-1-1:2005 is unconservative to design the column of modular. Therefore, a new method is necessary to design the proposed connection system with extensive work to be conducted in future research.